Copromyces bisporus, a new record for Venezuela - Delgado Avila, Adolfredo; Piñeiro Chávez, Albino; Urdaneta García, Lilia (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
On the basis, a study of coprophilous fungi from Zulia state, Venezuela, both a sordariaceous pyrenomycete with its verrucose spores and two- spored asci were isolated from rabbit and fox dung. The ascospores are uni or biseriate, without fixed orientation respected to the germpore; at first, they are hyaline, then ochraceous with a large globule, and finally dark brown, subglobose, furnished with short, broad, rounded warts and gelatinous equipment wanting. These features place the fungus in Copromyces, a genus characterized by nonstromatic, globose cleistotecia, usually aggregate, black, sparsely covered with hyaline, flexuous, septate hairs with indistinct paraphyses and irregularly clavate to cylindrical, short-stipitate, evanescent and unitunicate without apical ring asci. The specie was identified as Copromyces bisporus, which represents a new record for Venezuela.